Republic of Armenia : Staff Report for the 2002 Article IV Consultation, First and Second Reviews Under the Poverty Reduction and Growth Facility, and Request for Waiver of Performance Criteria. (IMF Staff Country Reports; Country Report, 2002)
This paper focuses on the Republic of Armenia's 2002 Article IV Consultation, First and Second Reviews Under the Poverty Reduction and Growth Facility (PRGF), and a Request for Waiver of Performance Criteria. The PRGF-supported program approved in 2001 focuses on revenue mobilization, the clearance of government arrears, and a decline in the deficit of the energy sector. Performance during the first year of the program was mixed. Tax collection was sluggish, and delays with structural reforms in the energy, water, and irrigation sectors led to the nonobservance of several quantitative performance criteria under the program.